The Prevention of Pesticide Risk Toxicity among Farmers on Food Estate Humbang Hasundutan - Mahyuni, Eka Lestari; Harahap, R. Hamdani; Harahap, Urip; Nurmaini (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This PPM activity is one of the community empowerment activities to increase the capacity of farmers, especially increasing safety and health behavior while using pesticides. The prevention program carried out in the form of a community movement to reduce the risk of pesticide toxicity is called GEMPAR (Gerakan Masyarakat Petani Atasi Racun). GEMPAR consists of eight action activities as a farmer movement in reducing the risk of toxicity due to the use of pesticides. GEMPAR in the PPM activity was carried out as a prevention effort which was promoted through FGD activities, demonstrations, and brainstorming. Farmers in the Food Estate are classified as farmers who work with the company so that the pattern of pesticide use is included in the regular category in determining the dose and type of pesticide used. However, the application of pesticides is still classified as very dangerous where direct contact with pesticides is very high. GEMPAR as a health solution responded very well and increased awareness of Food Estate farmers to improve pesticide use patterns. Each farmer acts as an agent of change who can comprehensively expand GEMPAR information through the promotion of the message of the eight GEMPAR actions which are divided into primary, secondary, and tertiary prevention actions.